Air emissions and health risk assessment around abattoir facility - Ebenezer Leke Odekanle; Omowonuola Olubukola Sonibare; Oludare Johnson Odejobi; Bamidele Sunday Fakinle; Funso Alaba Akeredolu (Heliyon, 2020)
The study assessed the impacts of abattoir activities on ambient air quality and health risk associated with exposure to PM2.5 and PM10, H2S, SO2 and NH3. Air samplings were done simultaneously around the abattoir at three points for sixty consecutive days (October to November) and standard methods adopted for the samplings and analysis. Health risks associated with exposure to PM10 and PM2.5 were estimated, using attributable fractions, relative risk and the excess lifetime cancer risk. The non-carcinogenic risks induced by the inhalation of H2S, SO2 and NH3 were also evaluated using hazard quotient (HQ). The results indicated that the average concentrations of 18.75 μg/m3, 89.17 μg/m3 and 0.1ppm for PM2.5, PM10 and NO2 respectively, were higher than the World Health Organization (WHO), National Ambient Air Quality Standard (NAAQS) and Federal Ministry of Environment (FMEnv) permissible limits. Air Quality Index showed that the ambient air quality in respect of CO and NH3 was very good, moderate for PM10 and was very poor for NO2 and SO2. It was also shown that 0.32% of deaths from lung cancer, and 0.23% from cardiopulmonary could be avoided if PM2.5 is reduced to 3 μg/m3 and while about 0.14% of all-cause mortality could be avoided if PM10 is reduced to 10 μg/m3. In similar manner, at least 0.45% likelihood that an individual in a group of people exposed to PM2.5 100m away from the burning point may have health issue (lung cancer) than an individual from another set of people that is exposed to baseline concentration of 3 μg/m3. All the HQ values exceeded the threshold value, set at the unity, implying that H2S, SO2 and NH3 are likely to cause adverse health effects in the area. Conclusively, continuous operation of this abattoir within the residential area can constitute a great environmental menace to the residents of the area and can result in complication to those with existing health challenge.